PEMAPARAN TEORI MANAJEMEN DAN AKUNTANSI PADA MASYARAKAT PANTAI NONGSA BATAM - Purba, Daris; Nasruji; Riki; Hendriati, Yossi; Rina; Julianti, Merline; Hazriyanto, Hazriyanto (ASOSIASI IDEBAHASA KEPRI, 2024)
Nongsa Beach is one of the tourist beaches that is integrated with residential communities. Many residents make beach tourism their livelihood. This service activity aims to convey management and accounting concepts to the Nongsa Beach community. The service method is the lecture method. Apart from delivering material, service activities were also followed by beach cleaning and distribution of basic food packages. The aim of this activity is to empower the community and for education for students. The service activity concluded that society needs management and accounting theory but it would be even better if it was packaged with ready-to-use technology.